To determine which expression is equal to \(5.1 \times 10^{-3}\), let's simplify each option one by one.
-
Option 1: \(2.2 \times 10^{-1} + 2.9 \times 10^{-2}\)
Convert \(2.2 \times 10^{-1}\) to a smaller power of ten:
\(2.2 \times 10^{-1} = 2.2 \times 10^{-1} = 22 \times 10^{-2}\)
Now we can add:
\(22 \times 10^{-2} + 2.9 \times 10^{-2} = (22 + 2.9) \times 10^{-2} = 24.9 \times 10^{-2} = 2.49 \times 10^{-1}\)
This does not equal \(5.1 \times 10^{-3}\). -
Option 2: \(3.9 \times 10^{-3} + 1.2 \times 10^{-3}\)
Adding these together:
\(3.9 \times 10^{-3} + 1.2 \times 10^{-3} = (3.9 + 1.2) \times 10^{-3} = 5.1 \times 10^{-3}\)
This equals \(5.1 \times 10^{-3}\). -
Option 3: \(2.9 \times 10^{-3} + 1.2 \times 10^{-3}\)
Adding these together:
\(2.9 \times 10^{-3} + 1.2 \times 10^{-3} = (2.9 + 1.2) \times 10^{-3} = 4.1 \times 10^{-3}\)
This does not equal \(5.1 \times 10^{-3}\). -
Option 4: \(3.5 \times 10^{3} + 1.6 \times 10^{-6}\)
These terms are vastly different in scale and their sum will not be anywhere near \(5.1 \times 10^{-3}\).
From the above calculations, the only expression that equals \(5.1 \times 10^{-3}\) is Option 2: \(3.9 \times 10^{-3} + 1.2 \times 10^{-3}\).